Facial diplegia: etiology, clinical manifestations, and diagnostic evaluation - Sefer Varol; Hasan Huseyin Ozdemir; Esref Akil; Demet Arslan; M. Ufuk Aluclu; Caner F. Demir; Yavuz Yucel (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective Facial diplegia (FD) is a rare neurological manifestation with diverse causes. This article aims to systematically evaluate the etiology, diagnostic evaluation and treatment of FD. Method The study was performed retrospectively and included 17 patients with a diagnosis of FD. Results Patients were diagnosed with Guillain-Barré syndrome (GBS) (11), Bickerstaff’s brainstem encephalitis (1), neurosarcoidosis (1), non-Hodgkin’s Lymphoma (1), tuberculous meningitis (1) herpes simplex reactivation (1) and idiopathic (1). In addition, two patients had developed FD during pregnancy. Conclusion Facial diplegia is an ominous symptom with widely varying causes that requires careful investigation.